PERILAKU SINTAKSIS BAHASA PONOSAKAN (SYNTACTIC OF PONOSAKAN LANGUAGE) - Sri Diharti (Balai Bahasa Sulawesi Utara, 2016)
The study discusses syntactic behavior on adjectival category. Adjektive is a word used to reveal nature or state of persons, objects, or animals. This study is aimed to describe or analyze adjectival types in Ponosakan language, such as mono-morphemic and poly-morphemic adjectives. Besides, this study is also describe syntactic behavior by looking at adjectives in the levels of phrase, namely adjectives as modifier, adjective as nuclei and pivot, and idiomatic adjective.The data anslysis performed by using contextual approach. Contextual approach is a way of analysis that applied on the data by basing, calculating, and connecting contexts. The result shows the use of adjectives in Ponosakan language based on types and levels of phrase.